Utilization of second opinion pathology consults by clinicians: a cross sectional study - Menkiti, Felix Emeka; Ukah, Cornelius Ozobia; Ukoha, Simdi Stephanie; Menkiti, Ifeoma Oluchukwu; Chigbo, Chisom God'swill; Uchendu, Ugochukwu Timothy; Mgbemena, Jude Ikwuakonam; Ezeike, Azuka Chinweokwu; Onyebuashi, Chinwendu; Uche-Okonkwo, Kenechukwu; Alozie, Chinonso; Nwakile, Peter Chukwudi; et al. (International Journal of Research in Medical Sciences, 2023)
Background: Pathology diagnosis is key to critical decision making in clinical medicine. In clinico-pathologic consults, there may be errors in pathologic diagnoses resulting in delayed or inappropriate treatment, hence impaired quality of care. Seeking a second opinion on a pathology consults is one procedure that enhances quality of healthcare services. In the spate of medical litigations, some doctors are either not aware of the procedure or do not utilize second opinion pathology consults (SOPCs). Methods: This cross sectional study used an online structured questionnaire to assess the awareness of and utilization of SOPCs by clinicians in Nigeria. Information regarding socio-demography, cadre, years in practice, reasons for utilization or non-utilization and modalities for seeking SOPCs were collected. Results: Of the 511 respondents, 75.7% of whom practiced in government-run tertiary hospitals, 33.5% have never utilised SOPC. Surgeons (29.7%) and gynaecologists (12.1%) are the major users of SOPCs; utilization of which is associated with cadre (p= 0.001) and not years of practice (p= 0.199). 24.3% divided specimen between pathologists, 15.5% sent a fresh specimen, 15.2% and 24.1% sent out the same slides and tissue blocks respectively, used for the first diagnosis. 65.8% SOPC requests were not accompanied with the first pathologist’s report. Conclusions: SOPC is an important component of a total quality assurance that helps reduce the overall cost of patient care. Many clinicians are not aware of SOPC procedure, hence the under-utilization. It is our opinion that proper enlightenment of clinicians will bridge this gap in knowledge and enhance better practice.